PENGARUH PENGAWASAN KEUANGAN DAERAH, TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH DAN AKUNTABILITAS TERHADAP KINERJA PEMERINTAH DAERAH KABUPATEN KLUNGKUNG - Putu Deddy Samtika Putra; Sang Ayu Putu Arie Indraswarawati (Jurnal Widya Akuntansi dan Keuangan, 2021)
This research was conducted by taking the location of the Regional Apparatus Organization (OPD) in the Klungkung Regency Government. The number of samples taken was 143 respondents. The method used was purposive sampling and through non-response bias sample testing. Data collection was carried out by distributing questionnaires. The research instrument used was the validity test and the reliability test. The analysis technique used is the classical assumption test and multiple linear regression analysis, determination analysis, F-test and t-test. From the results of the study, it is known that regional financial supervision has no effect on the performance of local governments at the Klungkung Regency Government, as evidenced by the t-count = 1.503 with a significance value of 0.135> 0.05, thus H1 is rejected. The transparency of regional financial management has a positive effect on the performance of local governments in the Klungkung Regency Government, as evidenced by the value of t-count = 4.365 with a significance value of 0.000, <0.05, thus H2 is accepted. Accountability has a positive effect on the performance of the local government at the Service in the Klungkung Regency Government, as evidenced by the t-count = 3.058 with a significance value of 0.003 <0.05, thus H3 is accepted.